2015
DOI: 10.1097/aci.0000000000000150
|View full text |Cite
|
Sign up to set email alerts
|

Local allergic rhinitis

Abstract: The possibility of a local occupational rhinitis should be considered in workers with a clear history of occupational rhinitis and negative immunological test, especially in the case of high molecular weight allergens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 43 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…81 In LAR patients, nasal symptoms, local sIgE production, and type 2 response-dominated inflammation in nasal mucosa can be induced during natural exposure to aeroallergens or by nasal provocation test (NPT). 82 …”
Section: Definition and Classificationmentioning
confidence: 99%
“…81 In LAR patients, nasal symptoms, local sIgE production, and type 2 response-dominated inflammation in nasal mucosa can be induced during natural exposure to aeroallergens or by nasal provocation test (NPT). 82 …”
Section: Definition and Classificationmentioning
confidence: 99%
“…Some ongoing mechanical and clinical investigations in AR are focused on how the Th2 cytokine microenvironment could affect and process AR-related pathology [4, 5]. Recent studies have shown that type 2 macrophages (M2) can influence IL-4 secretion and the IgE class switch process in cedar pollen-sensitized AR mice [6, 7], which suggests that M2 macrophages might have a role in the initiation and development of AR.…”
Section: Introductionmentioning
confidence: 99%
“…They have also been used to investigate local nasal allergic responses (87), although there is a need for additional studies to evaluate the sensitivity and specificity of the test.…”
Section: Methodsmentioning
confidence: 99%